A study of bio-hybrid silsesquioxane/yeast: Biosorption and neuronal toxicity of lead - Trama-Freitas, Bianca [UNESP]; Freitas, Johnattan C.S. [UNESP]; Martins, Rui C.; Gando-Ferreira, Licínio M.; Quinta-Ferreira, Maria Emília; Quinta-Ferreira, Rosa Maria; do Carmo, Devaney R. [UNESP] (Elsevier, 2017)
Lead is a heavy metal of high impact for the environment as well as for human health, being cause of several diseases. Considering the importance of obtaining an effective treatment for lead removal, a new hybrid material was developed for sorption of Pb2+ from aqueous solution. The effect of pH, temperature, liquid/solid ratio (g/cm3) and lead concentration on the sorption capacity of yeasts chemically modified with cubic silsesquioxane (YS) was analyzed. Additionally, the toxicity of lead on the neuronal activity was also investigated in order to assess whether the damage caused by the Pb2+ ion is reversible or not. The YS is highly promissory as sorbent of lead in high concentrations (100 and 500 ppm), reaching high efficiency in short contact times (15 min), and at the natural pH (4) of the Pb2+ solution and room temperature. The best sorption obtained was 82% removal and 248 mg/g with 500 cm3/g sorbent, pH 4, room temperature and contact time of 15 min. Besides, such high efficiencies are obtained with low quantities of biosorbent, when compared with other similar materials. The impact of lead on neuronal function was studied by measuring autofluorescence signals, associated with changes in cellular metabolism, at the hippocampal CA3 area in brain slices. In this toxicity tests, the effect of low concentrations of lead (1 and 3 μM) on neuronal activity was evaluated. After removal of the lead, the irreversibility of the observed changes can be verified, which suggests the existence of neuronal damages.
Keywords: Autofluorescence; Biosorption; Lead; Neuronal toxicity; Silsesquioxane; Toxicity; Yeast